Discovering the performance criteria of education development centers of medical sciences universities: A qualitative study - Mansoureh Taghavinia; Mohammad Reza Maleki (Wolters Kluwer Medknow Publications, 2020)
CONTEXT: Performance is a significant objective of any organization. To grow and develop and to improve the performance of the education development centers (EDCs) of medical sciences universities at Iran, the recognition of the performance criteria of these centers is important. This study was conducted with the aim of discovering the performance criteria of EDCs of medical science universities. SUBJECTS AND METHODS: This study was conducted using qualitative research and a semi-structured interview. Participants were selected using an expert sampling method is a sub-type of purposive sampling. Twenty-three faculty members and expert staff (11 males and 12 women) participated in the interview. Data were collected using the participant's perception. The data analysis was performed based on the interpretative analysis steps of Gillham and Rubin. RESULTS: From the analysis of data, seven categories including leadership, strategy, stakeholders, workforce, knowledge management, processes management, and results were obtained. CONCLUSIONS: The obtained criteria in this study assist managers to design and to develop self-assessment questionnaires and a performance measurement program for EDCs of medical sciences universities. This will facilitate performance evaluation of EDCs.